An effective means of drag reduction in high enthalpy flow through unsteady energy deposition. (September 2021) - Kumar, Shailendra; Kulkarni, Vinayak
Abstract: Numerical investigations are carried out to assess the performance of unsteady energy and steady energy depositions in the supersonic reacting flow. For this, a finite volume-based structured inviscid axisymmetric flow in-house solver is employed. This solver accounts for 5 species (O 2, O, N 2, N, and NO) and 11 chemical reactions. Initially, unsteady simulations are carried by depositing energy pulse upstream of the standing bow shock ahead of a sphere. With time, this pulse advances, grows and interacts with the bow shock. Both perfect gas (PGS) and reacting gas solvers (RGS) are used for this analysis. It has been noted that RGS based predictions show lesser stagnation pressure and thus wall pressure at the same interaction time. It has also been found that better drag reduction depends on the strength of low-density vortex which is formed due to the interaction between shock wave and blast wave. This vortex is stronger for the perfect gas case and thus portrays higher reduced propulsion energy or power effectiveness as compared to RGS based prediction. Simulation with the higher freestream stagnation enthalpy (3.0 MJ/kg) shows that there is 90% decrement in the density of the pulse as compared to lower enthalpy case (0.3 MJ/kg). However, there is 60.5% increment in the pressure of cell or outer part of the pulse as compared to 0.3 MJ/kg case. Further, the diameter of the pulse also increases by 19.67% for this higher freestream enthalpy condition. It has been noticed that, lower density of the pulse leads to the formation of stronger vortex and thus deepens the first valley of drag signal with increases in the freestream stagnation enthalpy. The formation of such stronger vortex, introduces one more valley in the drag signal for 3.0 MJ/kg case, where, 152% higher power effectiveness is registered. But, for steady energy deposition power effectiveness decreases with the inlet stagnation enthalpy. In all, it is strongly recommended to use unsteady pulse deposition instead of steady one for drag reduction in high enthalpy flow situations. Graphical abstract: Highlights: Various flow features for perfect and real gas cases with unsteady energy deposition are compared. Strong vortex leads to higher power effectiveness for unsteady energy deposition. Lower recirculation at higher enthalpy decreases effectiveness for steady energy deposition.